Udvikling af kontekstuelle kirkelige praksisser i den lokale kirke - Dorte Lund Kappelgaard (Svensk Teologisk Kvartalskrift)
Through two action research processes in a rural church and in a city church in the Evangelical Lutheran Church in Denmark, this article explores how the local church might develop contextually shaped church practices other than worship services. The processes are being shaped as they unfold. In the rural church, the volunteers and the employees in the development group have a shared church practice to reflect on while reaching out to Eastern Europeans in the local context. In the Copenhagen church, the volunteers have little shared religious language and practice and need to build a sense of mutual trust and shared practice experience to be able to create new practices together. Hartmut Rosa's notion of resonance and Hans-Georg Gadamer's notions of presuppositions and play are being used to make sense of these events through phenomenological descriptions and hermeneutical analyses of the exploration of formal and informal practices in the processes. Based on these analyses, I argue that there is a need for spaces of hermeneutical reflexivity, a need to listen for resonance, as well as a need for shared practice experiences to build on as a basis for the development of contextual church practices. Further, I suggest a broader understanding of and research on church practice, embracing spontaneous and informal practice, as well as to see meetings and development processes as spaces of potential church practice in themselves. Based on the two cases and Gadamer's notion of praxis, a new approach to church practice is developed that is sensitive to the dynamics of the often emergent, possibly fluctuant and non-instrumental character of meaningful practice related to church.